Screening of COVID-19 suspect cases in a Cargo Ship: A rare field experience - Madala, Praveen; Subramaniam, Senthilnathan (Indian Journal of Community Health, 2020)
Background: World Health Organization (WHO), China Country Office informed cases of pneumonia of unknown aetiology detected in Wuhan City, Hubei Province of China. On 7th January 2020, Chinese authorities identified a new strain of Coronavirus as the causative agent for the disease. By 1st April 2020, the disease since its first detection in China has spread to over 200 countries/territories leading to a total of 823626 confirmed cases and 40598 deaths. WHO declared the novel Coronavirus outbreak as a Pandemic on 11 March 2020 and named the 2019 novel Coronavirus as COVID-19. As the screening of these suspects in ships is a challenging and novel one, the present study was aimed at identifying the proper and systematic way of screening of these suspects. Screening if done systematically aids in early diagnosis of the COVID-19 suspects and if coupled with pre-arrival preparedness through e-mail follow up helps in proper planning. Proper risk communication can help in alleviating the fears of the stakeholders and public. Aims & Objectives: The primary objective of this study was to screen the COVID-19 suspect cases systematically in the vessels and the secondary objectives were to identify any gaps in the process of collection, transport and receipt of results of samples of COVID-19 Suspect cases, know the process of risk communication & to share the experience to other seaports for duplication. Materials & Methods: Screening was done for all the crew by the Investigators with proper Personal Protective Equipment (PPE) on the Bridge (Navigation Deck) of the vessel mainly for recording the temperature and eliciting other signs & symptoms of COVID -19. It was then followed by sending the samples of the two COVID-19 suspects for testing to the Government approved laboratory in a systematic way. Risk communication was also done to all the stakeholders and media in a well-coordinated manner at the earliest to update them on the facts and to prevent false communication. Results: Pre-arrival preparedness through screening of pre-arrival documents and systematic approach adopted for screening of the COVID-19 suspects led to early diagnosis of the suspects. Samples were collected as per protocol and sent for testing to the laboratory and reports of the same were obtained without any much constraints through proper liaison with Tamilnadu State Health team. Risk communication to the stakeholders and media prevented panic among the public and stakeholders. Conclusions: Pre-arrival e-mail follow-up and arrangements like coordination meeting with the stakeholders led to proper planning. Systematic screening and proper liaison with State Health team helped in the early diagnosis of the suspects. Proper and early risk communication to the stakeholders and media prevents panic, facilitates good support and prevents communication of maleficious information to the public.